Un procés sobre alcavoteria a la Montcada del segle XVI. - Conejero Pascual, Francisco José (Scripta, 2022)
In this research, a look is made towards the prostitution and gossiper in the society of the sixteen century Valencia. It is explored how the subject was treated by society at the time by a marginal group such as women prostitutes. Double morale in this case, causes contradiction in the stigmatization of the behavior of women engaged in this activity. Finally, i focuses on the case of Maca and her husband, inhabitants of Massarrojos and prosecuted for alcavoteria and other crimes.